Health gains with the intervention of rehabilitation nurses in patients with COPD - Costa, Fernando (2016)
COPD is a disease with high chronic morbidity rate, loss of quality of life and mortality. It is thought that by 2030 COPD will be the third cause of mortality worldwide. The rehabilitation nursing plays a key role in maintaining the functional capacity of the patient with COPD, for its impact on their quality of life. The aim of this study is to evaluate the gains in QOL in patients with COPD who had intervention of rehabilitation nurse, compared to patients who did not have intervention of rehabilitation nurse.